Relative Bioavailability and Bioequivalence Study of Theophylline Sustained Release Formulations - Vergin, Hartmut; Mahr, Gerhard; Winterhalter, Bernd; Wigand, Rainer (Arzneimittelforschung, 2003)
The objective of this study was to determine the bioequivalence of two theophylline (CAS 58-55-9) sustained release formulations containing 400 mg ( Theophyllin 400 retard Heumann, formulation A) and 375 mg (formulation C) theophylline, respectively. In addition, the relative bioavailability of the sustained release formulations in comparison to an oral solution (formulation B) was investigated. Twenty-four healthy male volunteers participated in the open randomized threeway crossover study. Multiple doses of the formulations were administered during three study periods of four days each (A: 400 mg once daily; B: 133 mg t.i.d.; C: 375 mg once daily). The absorption kinetics and the bioavailability of theophylline were investigated by model-independent and deconvolution methods. The relative bioavailability of formulation A as compared to the solution was 72 %. The oral sustained release capsules did not exhibit any differences with respect to AUCss,τ and Css,max whereas differences were detected regarding tss,max and peak trough fluctuation indicating minor deviations of the plasma profiles of both formulations. However, 90 % confidence intervals of the ratios of AUCss,τ and Css,max were within the respective acceptance limits. Thus, both formulations are bioequivalent considering rate and extent of absorption.
Keywords: CAS 58-55-9; Theophylline, bioequivalence, relative bioavailability, sustained release formulations; Theophyllin 400 retard Heumann, bioequivalence, relative bioavailability